Safety Evaluation of Elderly Laparoscopic Cholecystectomy - Bijan Khorasani; Ahmadali Akbari kamrani; Shahram Nazari; Khatib Semnan (University of Social Welfare & Rehabilitation Sciences, 2008)
Objectives: The most common indication for abdominal surgery in elderly (65 & older) is gallstone disease.The elderly are more prone to complication of such surgery due to their other co-morbidity and thus they may benefit mostly from a safer method of surgical procedure. The purpose of this study was to evaluate the safety and outcome of laparoscopic cholecystectomy in elderly compare to the conventional method. Methods & Materials: Via prospective study from June 2005 to March 2008 included all patient older than 60 years of age who underwent cholecystectomy by open (Group A) and laparoscopic (Group B) method in Milad Hospital.The demographic data (sex age), American Society of Anesthesiologists’ (ASA) score, postoperative mortality morbidity, length of stay and operative time were recorded for each patient and were compared between two methods. Data of patient’s analysis by SPSS with chi-square and t test. Results: The study included 311 elderlies (34% men and 66% women). Hundred fifty-seven patients underwent open cholecystectomy; 154 patients underwent laparoscopic cholecystectomy. The mean age was 7141 years. The outcome in group B (laparoscopic) included: morality 0%, morbidity 2%, postoperative hospital stay 1 days, mean operation time was 40 minutes. In group A(open): mortality and morbidity rate were 21% and 12% respectively with postoperative hospital stay 331 days and similar operation time as group A. Conclusion: Laparoscopic cholecystectomy is the gold standard treatment and safe procedure in elderly patient and aging is not considered to be a contraindication laparoscopic surgery in such patients.